2004
DOI: 10.1108/14626000410519155
|View full text |Cite
|
Sign up to set email alerts
|

The effects of regional capital subsidies on firm performance: an empirical study

Abstract: Capital subsidization is a widespread instrument of regional and industrial policy in Europe. A number of recent works have examined the influence of capital subsidization on the total factor productivity of recipient sectors and firms, and have provided strong evidence of neutral or even negative effects. The present study examines the effect of capital subsidization on four dimensions of the financial performance of firms, that is efficiency, profitability, capital structure, and growth, and provides evidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
44
2
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(69 citation statements)
references
References 33 publications
9
44
2
6
Order By: Relevance
“…By contrast, higher subsidies reduce the firms" reliance on external capital, which leads to higher stock prices. Our results are the opposite to those reached by Tzelepis and Skuras (2004) who analyze the impact of investment subsidies on firms" performance in the Greek food and drinks manufacturing sector. Their results document that subsidies do not have any significant effect on firms" efficiency, profitability and leverage, while capital subsidization is an effective industrial policy in promoting firms" growth which is refected upon firms" higher stock prices.…”
Section: Baseline Resultscontrasting
confidence: 56%
“…By contrast, higher subsidies reduce the firms" reliance on external capital, which leads to higher stock prices. Our results are the opposite to those reached by Tzelepis and Skuras (2004) who analyze the impact of investment subsidies on firms" performance in the Greek food and drinks manufacturing sector. Their results document that subsidies do not have any significant effect on firms" efficiency, profitability and leverage, while capital subsidization is an effective industrial policy in promoting firms" growth which is refected upon firms" higher stock prices.…”
Section: Baseline Resultscontrasting
confidence: 56%
“…Gleason, among others, found that firm size has a positive and significant effect on firm performance ROA. In contrast, many other researchers such as Mudambi and Nicosia, (1998), Lauterbach and Vaninsky, (1999), Durand and Coeuderoy, (2001), and Tzelepis and Skuras, (2004) The capital structure for firms varies from one sector to another and so do their optimal capital structures (see Bradley, Jarrell and Kim, 1984). Also, a firm's growth and business cycle varies from one industry to another (see for instance, Wei, Xie, and Zhang, 2005).…”
Section: Empirical Model and Proxies Variablesmentioning
confidence: 83%
“…S použitím panelových dát uvedené skúmajú napríklad Bergström (2000) a Tzelepis, Skuras (2004) alebo Duch, Montolio, Mediavilla (2009). V podmienkach Českej republiky analyzuje vplyv dotácií z EÚ na konkurencieschopnosť fi riem napríklad Sedláček (2011Sedláček ( , 2012 a Sedláček, Suchánek (2013).…”
Section: Súčasný Stav Poznaniaunclassified